2020
DOI: 10.1111/jop.13089
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and treatment outcome prediction for oral cancer

Abstract: Background The natural history of oral squamous cell carcinoma (OSCC) is complicated by progressive disease including loco‐regional tumour recurrence and development of distant metastases. Accurate prediction of tumour behaviour is crucial in delivering individualized treatment plans and developing optimal patient follow‐up and surveillance strategies. Machine learning algorithms may be employed in oncology research to improve clinical outcome prediction. Methods Retrospective review of 467 OSCC patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 25 publications
(26 reference statements)
2
42
0
Order By: Relevance
“…It would seem reasonable to consider these metrics as a benchmark given the robust nature of the study. The best performing model, Decision tree classifier from the present study, displayed comparable accuracy (76%) and ROC‐AUC score (0.77) to Karadaghy et al Other recent studies have found Decision tree algorithms to perform strongly when applied to predicting OSCC outcomes 20,21 …”
Section: Discussionsupporting
confidence: 60%
“…It would seem reasonable to consider these metrics as a benchmark given the robust nature of the study. The best performing model, Decision tree classifier from the present study, displayed comparable accuracy (76%) and ROC‐AUC score (0.77) to Karadaghy et al Other recent studies have found Decision tree algorithms to perform strongly when applied to predicting OSCC outcomes 20,21 …”
Section: Discussionsupporting
confidence: 60%
“…In this study, our approach considered two methods to yield a predictive model for treatment non-response using a sample of patients who had previously received silver diamine fluoride for dental caries. While research using machine learning in oral epidemiology is limited, previous studies have successfully applied ML-approaches to predict malodor using salivary microbiota [ 23 ], hypertension from gingival inflammation [ 24 ], oral cancer [ 25 ], oral poliovirus vaccine immunogenicity [ 26 ], temporomandibular joint osteoarthritis, and radiographic detection of tooth and dental restorations [ 27 ]. Notably, a recent review concluded that artificial intelligence, particularly machine learning and deep learning, can use data from the oral microbiome to predict systemic disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning models have achieved rapid development and are widely used in learning modeling and medical case prediction [ 19 21 ]. The systems are made up of three major parts, which are: (1) model: the system that makes predictions or identifications; (2) parameters: the signals or factors used by the model to form its decisions; (3) learner: the system that adjusts the parameters – and in turn the model – by looking at differences in predictions versus actual outcome.…”
Section: Discussionmentioning
confidence: 99%